2019
DOI: 10.3390/su11247128
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Human Gains—A New Approach of the Estimation

Abstract: Human health is dependent on the Indoor Air Quality (IAQ) of residential and public buildings, where people spend a substantial amount of time. Part of IAQ parameters, like temperature or humidity influence the thermal comfort of users, whereas too high carbon dioxide concentration (CO 2 ) could cause various complaints or diseases. In buildings like offices and schools, where we have a brush with a high density of users, the main source of CO 2 is simply people. The type of their activity brings higher or low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Currently, the recommended level of CO 2 is <3000 ppm when exercising [ 15 ]. Outdoor CO 2 concentration is 350 ppm, and the indoor level is usually 700 ppm above outside levels, reaching 2800 ppm and provoking no severe symptoms [ 31 ]. The combined chronic effect of hypoxia and high CO 2 during exercise must be explored in the future, based on recent evidence suggesting some issues when exposed to hypercapnic and hypoxic environments [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the recommended level of CO 2 is <3000 ppm when exercising [ 15 ]. Outdoor CO 2 concentration is 350 ppm, and the indoor level is usually 700 ppm above outside levels, reaching 2800 ppm and provoking no severe symptoms [ 31 ]. The combined chronic effect of hypoxia and high CO 2 during exercise must be explored in the future, based on recent evidence suggesting some issues when exposed to hypercapnic and hypoxic environments [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results, athletes, coaches, medical staff, and other stakeholders should address the differences between performing RST using a tent and using a mask when simulating hypoxia. It should be known that repeated-sprint workouts represent a challenge to the body that is exacerbated under hypoxic conditions and could be boosted by other environmental factors such as high CO 2 levels and the rise in WGBT [ 31 , 39 ]. Some studies have suggested that combined hypoxic and heat stress should be explored more in-depth [ 40 , 41 ] Despite the steady increase in WGBT inside the tent, the isolated and controlled conditions of this study did not allow the WGBT to rise to hazardous temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them take into account the amount of CO 2 generated by a person. A person's CO 2 emission has in fact been defined in different studies [22] , [23] , [24] , [25] . A healthy person, on a normal diet, generates an amount of CO 2 that can be expressed as ( eq.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Other results, such as those obtained in [25] , show that these values may differ according to the region. In addition, [22] presents experiments under different conditions with the aim of obtaining a measurement of the amount of CO 2 based on experimental measurements.…”
Section: Background and Related Workmentioning
confidence: 99%
“…This reflects the fact that in a real scenario the infiltration may have small deviations from the true value [36]. Similarly, the CO 2 generation per occupant in the room, c CO 2 occ , in any case cannot be a crisp value, since it strongly depends on factors, such as the type of work that an occupant performs during its presence in the room, the age of the occupant, the gender of the occupant, and various physical characteristics [37,38]: a young child's carbon dioxide generation differs from an adult heavy worker's.…”
Section: Fuzzy Occupancy Estimationmentioning
confidence: 99%